PENGARUH PIJAT OKSITOSIN TERHADAP KELANCARAN PENGELUARAN ASI PADA IBU POSTPARTUM DI WILAYAH KERJA PUSKESMAS BENER KABUPATEN PURWOREJO - Zuliyanti, Nurma Ika; Romadzona, Hidayatul; Agustiningsih, Agustiningsih (Jurnal Kebidanan, 2024)
ABSTRACTBackground: An ideal source of nutrition with a balanced composition and adapted to the baby's needs is breast milk (mother's milk). In primigravida postpartum mothers, breast milk usually does not come out smoothly. There are 52 postpartum mothers in the Bener Community Health Center working area, 23 of whom are not breastfeeding well. One of the efforts made to increase and make breast milk production smooth is by doing oxytocin massage. Research objective: to determine the effect of oxytocin massage on the smooth flow of breast milk in postpartum mothers in the working area of ??the Bener Health Center, Purworejo Regency. Research Method: Pre-experimental research with a One Group Pretest-Posttest design, a population of 52 postpartum mothers and a sample of 23 postpartum mothers. Purposive sampling technique. The research was conducted in August-September 2024. Data analysis used the Paired T-Test. Research Results: there is an effect of oxytocin massage on the smooth release of breast milk in postpartum mothers with a t value of –28.471 and a probability of 0.000 (smaller than alpha 0.05). Conclusion: There is an effect of oxytocin massage on the smooth flow of breast milk in postpartum mothers Key words: oxytocin massage, postpartum mothers, breast milk production.